2007
DOI: 10.1111/j.1365-3164.2007.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐based veterinary dermatology: a systematic review of interventions for treatment ofPseudomonasotitis in dogs

Abstract: The efficacy and safety of pharmacological interventions to treat canine Pseudomonas otitis externa and media were evaluated based on the systematic review of clinical trials published between 1967 and 2006. Clinical trials were included if Pseudomonas species were cultured from the ears of dogs with otitis externa or otitis media prior to treatment, and if the outcome of these interventions was reported at the end of the study. Studies were compared with regard to design characteristics (randomization generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 18 publications
1
56
1
4
Order By: Relevance
“…This is consistent with the observations of trial quality from systematic reviews of trials involving dogs and cats. [3][4][5][6] Our appraisal template was based on the CONSORT statement, which was developed to include items where there was empirical evidence of an association with bias in studies in human medicine, or where the information was deemed essential by the CONSORT development group for evaluating the external validity of trial findings. 22 The descriptive results (Table 1) serve as a guide to trial components that are poorly reported and require consideration when writing trial reports for publication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the observations of trial quality from systematic reviews of trials involving dogs and cats. [3][4][5][6] Our appraisal template was based on the CONSORT statement, which was developed to include items where there was empirical evidence of an association with bias in studies in human medicine, or where the information was deemed essential by the CONSORT development group for evaluating the external validity of trial findings. 22 The descriptive results (Table 1) serve as a guide to trial components that are poorly reported and require consideration when writing trial reports for publication.…”
Section: Discussionmentioning
confidence: 99%
“…2 Authors of systematic reviews of therapeutic interventions in dogs and cats also have reported shortcomings in the reporting of key features in the published research. [3][4][5][6] Numerous studies have reported shortcomings in the reporting of important methodological features of clinical trials in human clinical research. [7][8][9][10][11][12][13] Trials conducted without sound methodology are associated with biased treatment effects.…”
mentioning
confidence: 99%
“…Otitis is believed to be multifactorial and treatment can be difficult in some cases. [1][2][3] Common organisms isolated from dogs with otitis externa include Staphylococcus spp., Pseudomonas spp., Proteus spp., Streptococcus spp., Escherichia coli, Klebsiella spp., Bacteroides spp., Pasteurella spp. and Malassezia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from other systematic reviews (Nuttall et al 2007, Negre et al 2009, Pereira et al 2011, various data were classified as adequate (score: 3), unclear/partly adequate (score: 2) or inadequate (score: 1). Some parameters were classified only as adequate (score: 2) or inadequate (score: 1).…”
Section: Assessment Of the Quality Of Papersmentioning
confidence: 99%